Assessing the ovarian development of Macrobrachium amazonicum (Heller, 1862) phenotypes by means of an integrative analysis - Paschoal, Lucas Rezende Penido [UNESP]; Zara, Fernando José [UNESP] (Elsevier, 2023)
Macrobrachium amazonicum is a species of economic interest with a wide distribution in the Americas and high morphological and reproductive variability. Three phenotypes can be observed in this species: i) large-size amphidromous, ii) large-size and iii) small-size hololimnetic prawns. In the present work, the morphological, histochemical and ultrastructural aspects of ovarian development in the three phenotypes were comparatively analyzed. In addition, the interaction between the ovary and the hepatopancreas was investigated in these phenotypes through the use of gonadosomatic (GSI) and hepatosomatic (HSI) indices. Despite the morphological differences and different reproductive strategies adopted by the females, the macroscopic, histochemical and ultrastructural patterns of ovarian development showed no differences between the phenotypes. The ovaries were macroscopically classified into five stages of development (I to V). In early stages (I and II), the ovaries are full of oogonia, previtellogenic oocytes and oocytes in primary or endogenous vitellogenesis. At these stages, the rough endoplasmic reticulum (RER) produces a granular electron-dense material and sends it to the Golgi apparatus, where it will be modified, compacted and transformed into immature yolk granules. From stage III, secondary or exogenous vitellogenesis begins (with no interruption of endogenous vitellogenesis), where follicular cells nourish the oocytes and extracellular material is absorbed by endocytic vesicles, which fuse with immature yolk granules (forming mature granules) or with existing mature yolk granules. In stages IV and V, secondary vitellogenesis continues and mature yolk granules progressively occupy the cytoplasm. In M. amazonicum, the patterns of increase in oocyte diameter are quite similar between phenotypes, being greater in the small-size phenotype. This is related to the formation of larger oocytes/eggs and the production of large lipid reserves for their larvae. Changes in GSI and HSI during ovarian development show strong similarity between phenotypes, supporting the results obtained by histology and ultrastructure. Females in stages III and IV mobilize hepatopancreas reserves for ovarian maturation, which justifies the higher HSI values recorded in these stages. On the other hand, females in stage V show higher GSI and lower HSI values, indicating a mobilization of resources for the end of ovarian development as the females are ready to spawn.
Keywords: Amazon River prawn; Gonadosomatic index; Hepatosomatic index; Reproduction; Vitellogenesis